Manfaat Penerapan Manajemen Bakat dan Pengetahuan Dalam Optimalisasi Kinerja Pegawai (Studi Reflektif pada Biro Administrasi Umum, Perencanaan dan Keuangan (Kepegawaian) Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar): Manfaat Penerapan Manajemen Bakat dan Pengetahuan Dalam Optimalisasi Kinerja Pegawai (Studi Reflektif pada Biro Administrasi Umum, Perencanaan dan Keuangan (Kepegawaian) Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar) - Kadek, Kadek Suartini (Widyadewata, 2025)
This is a reflective study conducted by the researcher in regards of the position as a human resource analyst at the General Administration, Planning, and Finance Bureau of the I Gusti Bagus Sugriwa Hindu State University Denpasar. This reflective study was carried out on the basis that this religious Hindu state university is still in its early stages of development because the regulations governing its change of status are relatively new. One of the current issues is how to implement talent management and knowledge management for its employees. Career development, job rotation, and placement for certain positions have far been routine and have not fully adopted the mandates of the Law and its derivative regulations. This study was conducted using a literature review and scientific exploration as primary data, including legal sources, policies, and other relevant literature. In addition to regulatory analysis, interviews and observations were also conducted as supplementary data. The results of this study indicate that both of these management practices are indeed regulated in laws and regulations, and the previous studies also suggest that if talent management and knowledge management are applied well, they can optimize employee performance and contribute to achieving the institution's goals.